Inferring the Urban Transmission Potential of Bat Influenza Viruses - Giotis, Efstathios S. (Frontiers in Cellular and Infection Microbiology, 2020)
Bats are considered natural reservoirs of various, potentially zoonotic viruses, exemplified by the influenza A-like viruses H17N10 and H18N11 in asymptomatic Neotropical bats. These influenza viruses are evolutionarily distinct, are poorly adapted to laboratory mice and ferrets and cannot reassort in vitro with conventional strains to form new influenza subtypes. However, they have attracted renewed attention following reports that their entry in host cells is mediated by the trans-species conserved MHC-II proteins, suggesting that they hold zoonotic potential. Despite the recent studies, the viruses’ epidemiology and public health significance remain incompletely understood. Delineating the mechanistic basis of the interactions with their hosts and assessing their global distribution are essential in order to fully assess the zoonotic threat that these strains pose.